Surface runoff associated with climate change and land use and land cover in southeast region of Brazil - Arantes, Leticia Tondato [UNESP]; Carvalho, Ana Claudia Pereira; Carvalho, Ana Paula Pereira; Lorandi, Reinaldo; Moschini, Luiz Eduardo; Di Lollo, José Augusto [UNESP] (Elsevier, 2021)
Changes in climate and in land use/cover can compromises water resources availability and quality, conditioning the planning and management of these essential resources. The objective of this research was to understand the environmental dynamics of the studied region considering this context and to develop instruments for the best management of water resources, based on Potential Runoff Charts generated from natural and anthropic environment attributes consideration in the years 2001 and 2017. The study area was the Rio Claro Watershed (RCW), which covers 251.91 km² and is located in the northwest region of São Paulo State, Brazil. Analytic Hierarchy Process (AHP) was used to define weights of the environmental attributes: steepness; total annual rainfall; land use/cover; soil; landforms; and aquifer units. The charts present the surface runoff in five classes (Very Low, Low, Medium, High, and Very High). The results showed significant changes in the period, due to climate changes, and, secondly, due to land use/cover changes. While in 2001 the Low and Medium Potential classes (59.3%) predominated, in 2017 the Medium and Very Low Potential classes (56.5% total) were the most common. High and Very High Potential classes showed small variations in the two years. Results derivate especially from lower rainfall in 2017 compared to 2001, showing that climate changes does not always mean an increase in rainfall on a regional scale and that water resources management instruments should consider such situations. The proposed measures aim to favor infiltration, reduce erosive processes, and favoring aquifers recharge.
Keywords: AHP; GIS; Water resources; Watershed